Public Health Resilience Checklist for High-Consequence Infectious Diseases—Informed by the Domestic Ebola Response in the United States. Issue 6 (November 2018) - Sell, Tara Kirk; Shearer, Matthew P.; Meyer, Diane; Chandler, Hannah; Schoch-Spana, Monica; Thomas, Erin; Rose, Dale A.; Carbone, Eric G.; Toner, Eric
Abstract : Context: The experiences of communities that responded to confirmed cases of Ebola virus disease in the United States provide a rare opportunity for collective learning to improve resilience to future high-consequence infectious disease events. Design: Key informant interviews (n = 73) were conducted between February and November 2016 with individuals who participated in Ebola virus disease planning or response in Atlanta, Georgia; Dallas, Texas; New York, New York; or Omaha, Nebraska; or had direct knowledge of response activities. Participants represented health care; local, state, and federal public health; law; local and state emergency management; academia; local and national media; individuals affected by the response; and local and state governments. Two focus groups were then conducted in New York and Dallas, and study results were vetted with an expert advisory group. Results: Participants focused on a number of important areas to improve public health resilience to high-consequence infectious disease events, including governance and leadership, communication and public trust, quarantine and the law, monitoring programs, environmental decontamination, and waste management. Conclusions: Findings provided the basis for an evidence-informed checklist outlining specific actions for public health authorities to take to strengthen public health resilience to future high-consequence infectious disease events.